Trajectories of work disability and unemployment among young adults with common mental disorders - Magnus Helgesson; Petter Tinghög; Mo Wang; Syed Rahman; Fredrik Saboonchi; Ellenor Mittendorfer-Rutz (BMC, 2018)
Abstract Background Labour-market marginalisation (LMM) and common mental disorders (CMDs) are serious societal problems. The aims were to describe trajectories of LMM (both work disability and unemployment) among young adults with and without CMDs, and to elucidate the characteristics associated with these trajectories. Methods The study was based on Swedish registers and consisted of all individuals 19-30 years with an incident diagnosis of a CMD in year 2007 (n = 7245), and a matched comparison group of individuals without mental disorders during the years 2004-07 (n = 7245). Group-based trajectory models were used to describe patterns of LMM both before, and after the incident diagnosis of a CMD. Multinomial logistic regressions investigated the associations between sociodemographic and medical covariates and the identified trajectories. Results Twenty-six percent (n = 1859) of young adults with CMDs followed trajectories of increasing or constant high levels of work disability, and 32 % (n = 2302) followed trajectories of increasing or constant high unemployment. In the comparison group, just 9 % (n = 665) followed increasing or constant high levels of work disability and 21 % (n = 1528) followed trajectories of increasing or constant high levels of unemployment. A lower share of young adults with CMDs followed trajectories of constant low levels of work disability (n = 4546, 63%) or unemployment (n = 2745, 38%), compared to the level of constant low work disability (n = 6158, 85%) and unemployment (n = 3385, 50%) in the comparison group. Remaining trajectories were fluctuating or decreasing. Around 50% of young adults with CMDs had persistent levels of LMM at the end of follow-up. The multinomial logistic regression revealed that educational level and comorbid mental disorders discriminated trajectories of work disability, while educational level, living area and age determined differences in trajectories of unemployment (R2 difference = 0.02-0.05, p < 0.001). Conclusions A large share, nearly 50%, of young adults with CMDs, substantially higher than in the comparison group of individuals without mental disorders, display increasing or high persistent levels of either work disability or unemployment throughout the follow-up period. Low educational level, comorbidity with other mental disorders and living in rural areas were factors that increased the probability for LMM.